Efficacy of platelet-rich plasma lysate in patients with corneal erosion or post-traumatic scarring of the tissues of the eyelids - N. V. Borovkova; I. A. Filatova; E. V. Chentsova; E. V. Fedoseeva; Yu. A. Pavlenko; I. N. Ponomarev; S. A. Shemetov; A. O. Petrova (Российский офтальмологический журнал, 2020)
Purpose: to evaluate the effectiveness of platelet-rich plasma (PRP) lysate in patients with corneal erosion or posttraumatic scarring of eyelid tissues.Material  and methods. The study involved 30 patients aged 22 to 82 (51.5 ± 19.1 years): 10 with persistent corneal erosions, who were treated in 2 stages (2 weeks of standard keratoprotective therapy, then treatment supplemented  with instillations of PRP lysate) and 20 patients with post-traumatic  scarring of eyelid tissues, who were divided into a clinical group and a comparison group. PRP lysate was produced in the cell transplantation  and immunotyping  laboratory of N.V.  Sklifosovsky Research  Institute  for Emergency Medicine.Results. In group 1, already on the 3rd day of PRP lysate use, a positive dynamic of the cornea was observed: all patients had fewer complaints of pain, photophobia, and lacrimation. Corneal biomicroscopy, performed daily over the entire epithelization period, revealed a decrease in hyperemia of the tarsal and bulbar conjunctiva and corneal edema, which indicated a weakened inflammatory response. On average, the area of the cornea at the start of traditional therapy was 21.6 [19.6; 30.65] mm2. After two weeks of treatment, at the time of adding PRP lysate, the average area of erosion fell to 15.7 [12; 18.9] mm2, after a week of treatment with lysate, it dropped to an average of 2.35 [0.4; 4.3] mm2. On day 14, all patients revealed complete epithelialization  of the corneal defect. In patients with post-traumatic  eyelid tissue scars, after a 3-month-long use of PRP lysate (study group), an improvement  was noted in the cosmetic and functional  state of the eyelids, on average by 4 points (Me = 12 [10; 12] points before and 8.5 [8; 9] points after treatment (on the Manchester scar assessment scale), in contrast to the patients who received no anti-scar  therapy (comparison group), as the latter showed a deterioration in the condition of eyelid scars by 1–2 points (Me = 11 [10.25; 11.75] points at the beginning and 12 [11; 12] points at the end of the observation period). The acoustic density of scar tissue in the study group approached the normal values, in contrast to the comparison group, in which scar tissue appeared to be hypoechoic.Conclusion. Using PRP lysate aimed at improving the repair and regeneration processes in patients with corneal erosion or post-traumatic  scarring of eyelid tissues is promising and requires further clinical study.